Human Intestinal Bacteria Mediate Reduction of the N-Oxides of Isoline and Monocrotaline to the Corresponding Parent Alkaloids - Tang, Jun; Wang, Zhengtao; Akao, Teruaki; Hattori, Masao (Asian Journal of Chemistry, 2012)
The role of human intestinal bacteria in the biotransformation of pyrrolizidine alkaloid N-oxides was investigated. Two naturally-occurring hepatotoxic pyrrolizidine alkaloids, isoline and monocrotaline and their N-oxides were incubated with a human fecal suspension in an in vitro model, respectively. The metabolites were isolated and purified by chromatographic techniques and identified by the spectral analyses and the metabolic profiles were further analyzed by a specific TLC method. Human intestinal bacteria showed high reduction effects on the pyrrolizidine alkaloid N-oxides but not on the resultant tertiary alkaloids, suggesting that IB may play a partial role in the cyclic conversion between each pyrrolizidine alkaloid and its N-oxide in vivo. This evidence implied the potential risk of the pyrrolizidine alkaloid-containing Chinese medicinal herbs to human health when used in decoctions.